Methods of Organizational Conflict Management and the Leadership Styles Used by the Heads of Academic Departments at the University of Duhok - Abdullah , Bshkush Jahfar (Zanco Journal of Human Sciences, 2021)
The present study aimed to investigate the association between methods of organizational conflict management and the leadership styles used by the heads of academic departments at the University of Duhok. The study controls for gender, the academic title, years of service and the name of the college. The research population consisted of all the teaching staff at the University of Duhok, whose number is (1607). The researcher used multi-stage random sample of (240) male and female heads of departments. The researcher prepared two research instruments. The first one to measure organizational conflict management methods, which consisted of (20) items and divided into four themes: confrontation, avoidance, appeasement, and concession. The second instrument to measure the leadership styles, which consisted of (30) items distributed divided three themes: democratic, autocratic, and chaotic The results of this research reveal: 1. The two most used methods of organizational conflict management are avoidance and appeasement. 2. The two most leadership styles adapted by heads of departments are the autocratic and the chaotic styles.3. There is a statistically significant relationship between the democratic style and confrontation, appeasement, and compromise methods.4. The relationship between the chaotic style and the avoidance methods is statistically not significant.